A filtered high gain observer for a class of non uniformly observable systems – Application to a phytoplanktonic growth model. (March 2020) - Robles-Magdaleno, J.L.; Rodríguez-Mata, A.E.; Farza, M.; M'Saad, M.
Highlights: A standard high gain observer for non uniformly observable systems has been redesigned to account for high fequency signals. The behaviour of the proposed observer with respect to measurements noise is significantly improved. The performance and main properties of the observer are highlighted through a phytoplanktonic growth model. Abstract: The design of a high gain observer with filtering capabilities for a class of non uniformly observable systems is proposed. The filtering feature enables to perform a smooth estimation in the presence of noisy output measurements. Of fundamental interest, the Filtered High Gain Observer (FHGO) design is first carried out by assuming that the output measurements are available in a continuous manner before being extended to the case of sampled outputs leading thereby to a continuous-discrete time FHGO which inherits the main properties of the original FHGO. The performance of the FHGO and its main properties are highlighted and compared to those of a Standard High Gain Observer (SHGO) through a bioprocess dealing with the growth of a phytoplanktonic population.